Synthetic ground motions to support the Fennoscandian GMPEs. Supporting information – Response spectra dataset in excel format - Fülöp, Ludovic; Jussila, Vilho; Fälth, Billy; Voss, Peter; Lund, Björn (Zenodo, 2019)
This dataset has been created in the NKS project: ”Synthetic ground motions to support the Fennoscandian GMPEs”, contract: NKS-R(18)126/5. The data is RotD50 (Boore, 2010, doi: 10.1785/0120090400 ), pseudo-acceleration response spectra calculated from synthetic ground motions generated using physics-based modeling of Fennoscandian earthquakes. The earthquake magnitude range is 4.3-5.6; the rupture distance range 2-30km and the hypocenter depth range 2-20km. The response spectra is in mm/s2 and should be used up to 25Hz. Cite the data as part of the research report: Fülöp, L., Jussila, V., Fälth, B., Voss, P., Lund, B. 2019. Synthetic ground motions to support the Fennoscandian GMPEs. NKS - Nordic Nuclear Safety Research NKS-424, ISBN: ISBN 978-87-7893-514-4 Methods used to generate the data are described in: Fülöp, L., Jussila, V., Lund, B., Fälth, B., Voss, P., Puttonen, J., Saari, J., and Heikkinen, P. 2017. Modelling as a Tool to Augment Ground Motion Data in Regions of Diffuse Seismicity – Final report. NKS - Nordic Nuclear Safety Research NKS-394, ISBN: 978-87-7893-482-6 Fülöp, L., Jussila, V., Lund, B., Fälth, B., Voss, P., Puttonen, J., Saari, J., 2016. Modelling as a tool to augment ground motion data in regions of diffuse seismicity - Progress 2015. NKS Nordic Nuclear Safety Research, ISBN: 978-87-7893-448-2 Funding from: Nordic Nuclear Safety Research, Project NKS-R(18)126/5